Essential Oil Disinfectant Efficacy Against SARS-CoV-2 Microbial Surrogates - Bailey, Emily S.; Curcic, Marina; Biros, Jnev; Erdogmuş, Hüseyin; Bac, Nurcan; Sacco, Albert (Frontiers in Public Health, 2021)
Reports of COVID-19 cases potentially attributed to fomite transmission led to the extensive use of various disinfectants to control viral spread. Alternative disinfectants, such as essential oils, have emerged as a potential antimicrobial (1-3). Four essential oil blends were tested on three different surfaces inoculated with a coronavirus surrogate, bacteriophage Phi 6, and a bacterial indicator, Staphylococcus aureus. Log10 concentration reductions were analyzed using GraphPad Prism software. Data collected in this study show that the application of dilute essential oil disinfectants using a spray delivery device is an effective way to reduce concentrations of bacterial and viral microorganisms on ceramic, stainless steel, and laminate surfaces. Surrogate viruses were reduced up to 6 log10 PFU and bacterial were reduced up to 4 log10 CFU. Although surfaces are no longer considered a high risk fomite for COVID-19 transmission (4), the disinfection of microorganisms on surfaces remains an important consideration for high touch areas in hospitals, waiting rooms, etc. The application of spray disinfectants, based on essential oil blends, provides a rapid and effective means to reduce microbial contamination on high-touched surfaces.